Air Polishing and CHX Effects in Addition to Subgingival Ultrasonic Instrumentation on Clinical Periodontal Parameters: A Randomised Clinical Trial - Caygur, Ayse (Journal of Contemporary Medical Sciences, 2020)
Objectives: This study was performed to investigate the efficacy of using glycine powder air-polishing (GPAP) or antiseptics (CHX) adjunctively to scaling and root planing (SRP) in the treatment of periodontitis. Methods: In this trial, ninety patients (between 28-80 years old) who had at least three teeth with 3 to 7- mm periodontal pockets, were ıncluded from the Department of Periodontology. The patients were divided into three groups randomly. In the control group ultrasonic instrumentation was performed with distilled water and hand instrumentation, in the CHX group ultrasonic instrumentation was performed with CHX and hand instrumentation, in the GPAP group in addition to SRP with ultrasonic performed with distilled water and hand instrumentation, GPAP was performed for 10 seconds per periodontal pocket using a Perio-Flow device. All treatments were performed in one session. Resuls: The scores of plaque index(PI),gingival index (GI), probing depth (PD), bleeding on probing (BOP) and clinical attachement level (CAL) were decreased in all groups after 1 month and the results were statistically significant in intergoup comparisions. PI and CAL scores were statistically significant in intragroup comparisions in GPAP group. Altough GI, PD and BOP scores were lower in the GPAP group than CHX and control group, the differences after 1 month were not statistically significant. Conclusion: Within the limits of this study, it was seen that SRP was effective alone in the treatment of periodontitis. However, using a CHX with ultrasonic devices has little beneficial effects on periodontal parameters when compared with control and GPAP groups. GPAP groups was found more effectively in PI and CAL scores.